Mother of One to Mother of Two: A Textual Analysis of Second-Time Mothers’ Posts on the BabyCenter LLC Website - Beyers-Carlson, Emma; Schoenebeck, Sarita; Volling, Brenda L. (Frontiers in Psychology, 2022)
Mothers use online resources frequently to obtain information on pregnancy, birth, and parenting. Yet, second-time mothers may have different concerns than first-time mothers given they have a newborn infant and another child at home. The current study conducted an on-line qualitative analysis of the posts of second-time mothers during pregnancy and the first months postpartum on the BabyCenter LLC website, one of the largest online parenting communities. Latent Dirichlet Allocation (LDA) analysis on roughly 16,000 posts to BabyCenter birth clubs in 2017 by approximately 4,000 users revealed second-time mothers relied on the online support of the BabyCenter community to share and discuss topics of pregnancy, birth, and child rearing. Second-time mothers also raised questions about preparing their firstborn children for a new baby sibling, how they would care for two children, whether they would love the second one as much as the first, and how the second child would change family dynamics. Future research needs to recognize that second-time mothers may have distinct concerns surrounding the birth of their second child, and antenatal education and parenting classes may need to be modified to be more inclusive of these women’s needs and perspectives. Online parenting communities offer avenues to support women as they make the transition from one child to two and may provide targeted opportunities to disseminate evidence-based practices that can assist women and their children.